Comprehensive Quantitative Characterisation of Single Crystal Alloys. Issue 1 (September 2020) - Nenchev, B; Strickland, J; Perry, S; Tassenberg, K; Gill, S
Abstract: Classically, the primary dendrite arm spacing (PDAS) is used as a gauge to determine the quality of a single-crystal alloy. However, this length scale varies substantially over a cast due to variation in the thermo-solutal conditions. In this work, several dimensionless parameters are derived that characterise this variation based purely on geometrical and natural pattern formation. They are determined by applying a novel shape limited spacing algorithm (SLPS). SLPS accurately evaluates the relationship between local PDAS and packing pattern formations, offering a new method of single crystal analysis. The SLPS algorithm is a part of DenMap, a dendrite core feature extraction tool designed to significantly speed up single-crystal characterisation for process optimisation and standardisation for academia and industry.